Implementation of pedagogical solutions to increase the efficiency of the digitalization of learning at the university - Kazimova, D.A.; Tussipkhan, A.; Adilkhan, G. (KU Publ., 2021)
The article discusses the implementation of digital technologies in the higher education system, which opens up new opportunities for the design of new pedagogical solutions. The authors highlight the ways to create a digital educational space and content application through digital technologies. The main directions of implementation of pedagogical solutions to improve the results of the teaching and learning process in the context of digitalization of education are described. The main areas of application of ICT tools in the educational process of the University for improving the content of teacher education are considered, formation of a high level of information culture. The means of using interactive innovative technologies, automated systems are analyzed, allowing to equip with new information arrays of resource support of the university, for the competent use by teachers of the potential of modern information technologies for solving practice-oriented tasks of professional activity. All of these diverse methods and approaches, selected by the authors contribute to the development of students ' creative abilities, mastering new technologies.
Жоғары оқу орындарында оқытуды цифрландыру процесінің тиімділігін арттыру мақсатында педагогикалық шешімдерді іске асыру
Реализация педагогических решений в целях повышения эффективности процесса цифровизации обучения в вузе
Keywords: digital technologies; pedagogical solutions; digital educational space; digitalization of education; innovative technologies; Information Technology; digital pedagogy; information resource